Pigou's advice and Sisyphus' warning: Carbon pricing with non-permanent carbon-dioxide removal - Max Franks; Matthias Kalkuhl; Friedemann Gruner; Kai Lessmann; Ottmar Edenhofer (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2026)
This paper develops a welfare and public economics perspective on optimal policies for carbon removal and storage (CDR) in permanent and non-permanent sinks. Non-permanent CDR reduces mitigation costs, even though the stored carbon is released into the atmosphere eventually. It may serve as bridge technology until permanent CDR becomes available. In contrast to permanent removals, non-permanent CDR does not reduce the optimal long-run temperature level. Its valuation differs from the social cost of carbon since a social cost of carbon removal arises from marginal damages caused by emissions released from non-permanent storage. We discuss three policy regimes that ensure optimal deployment of non-permanent CDR in terms of their informational and institutional requirements for monitoring, liability, and financing.
Keywords: D61; H23; Q54; Q58; 330; carbon dioxide removal; carbon capture; social cost of carbon; climate policy; impermanence